Conocimiento de las medidas de seguridad vial y su influencia en la prevención de traumas por accidentes de tránsito en la parroquia Catamayo - Monge Barrera, David (2019)
Road safety is understood as the prevention of traffic accidents or the minimization of their effects, which can compromise the life and health of people, since every human being has the need to move from one place to another, makes this The problem is not only limited to those who exercise as drivers but rather involves all citizens in general, as some time a person can become a pedestrian, driver or user of public or private transport, becoming a population potentially at risk of suffering a traffic accident and derived from these traumas such as: cuts, dislocations, fractures, among others. It is a prospective, transversal and analytical-descriptive study, for which a survey was used as a tool that was applied to a sample of 378 people from a universe of 23453 inhabitants of the Catamayo parish, whose objective is to collect information regarding how much the population of this parish knows about road safety to prevent the traumas caused by traffic accidents, resulting in 88.4% being aware of road safety measures, while 11.6% is not. This means that the population of the Catamayo parish has knowledge about road safety measures, however, there is a minority that does not know about it, therefore, this translates into a risk factor of suffering a traffic accident and with it is a trauma that puts your health and your life at risk. Keywords: Health, Mobility, Risk, Fracture, Population.